Jupiter gravity field estimated from the first two Juno orbits. Issue 10 (25th May 2017) - Folkner, W. M.; Iess, L.; Anderson, J. D.; Asmar, S. W.; Buccino, D. R.; Durante, D.; Feldman, M.; Gomez Casajus, L.; Gregnanin, M.; Milani, A.; Parisi, M.; Park, R. S.; et al.
Abstract: The combination of the Doppler data from the first two Juno science orbits provides an improved estimate of the gravity field of Jupiter, crucial for interior modeling of giant planets. The low‐degree spherical harmonic coefficients, especially J4 and J6, are determined with accuracies better than previously published by a factor of 5 or more. In addition, the independent estimates of the Jovian gravity field, obtained by the orbits separately, agree within uncertainties, pointing to a good stability of the solution. The degree 2 sectoral and tesseral coefficients, C2, 1, S2, 1, C2, 2, and S2, 2, were determined to be statistically zero as expected for a fluid planet in equilibrium. Key Points: The Jupiter gravity field has been evaluated for the first two Juno orbits The zonal harmonics J4 and J6 improve over previous results by factors of 5 and 22, respectively, providing strong constraints on Jupiter interior models